Value of punishment for society (Journal of actual problems of jurisprudence, 2018)
In this article the concept of punishment opens up taking into account his importance for society. Punishments are means for establishing order in society, the aim of punishment is many-sided. An author underlines importance of punishment as facilities of warning and prophylaxis of offences.Key words: punishment, law, right, rule, discipline, customs, society, state.